Buried flexible pipes - Smith, G. N. (Contractor report (Transport and Road Research Laboratory) ; 228, 229, 230, 1991)
No. 1: Design methods presently used in Britain. - - No. 2: The analytical method developed by Gumbel for TRRL. - - No. 3: Application of a new design method.